2019
DOI: 10.1002/ddr.21589
|View full text |Cite
|
Sign up to set email alerts
|

iRGD‐paclitaxel conjugate nanoparticles for targeted paclitaxel delivery

Abstract: Paclitaxel (PTX) is a chemotherapeutic agent which shows antitumor activities against a broad spectrum of cancers. Yet, the current formulation of PTX used in clinic may cause a number of adverse reactions, which significantly limit its application. To obtain better clinical use of PTX, we report, for the first time, iRGD‐PTX conjugate nanoparticles (NPs) for targeted PTX delivery. iRGD‐PTX conjugate was synthesized from thiolated iRGD and 6‐maleimidocaproic acid‐PTX through Michael addition reaction. iRGD‐PTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The drug release behavior of TNP was determined as previously reported [ 25 , 26 , 27 , 28 ]. A PTX@TNP solution (1 mL, 200 μg of PTX) was added to a Float-A-Lyzer G2 dialysis device (100 kDa MWCO, Spectra/Por Dialysis Membrane, Repligen, Waltham, MA, USA) and then immersed in 10 mL of biological solution (PBS, pH = 7.4) containing 0.5% v / v Tween 80 to determine the sink condition of the drug.…”
Section: Methodsmentioning
confidence: 99%
“…The drug release behavior of TNP was determined as previously reported [ 25 , 26 , 27 , 28 ]. A PTX@TNP solution (1 mL, 200 μg of PTX) was added to a Float-A-Lyzer G2 dialysis device (100 kDa MWCO, Spectra/Por Dialysis Membrane, Repligen, Waltham, MA, USA) and then immersed in 10 mL of biological solution (PBS, pH = 7.4) containing 0.5% v / v Tween 80 to determine the sink condition of the drug.…”
Section: Methodsmentioning
confidence: 99%
“…Different RGD peptides were also used in the literature. Xu et al reported the conjugation of PTX with iRGD peptide (CRGDKGPDC), forming NPs by dialysis [174]. In another study, Liu et al reported a simple PTX conjugate by using tumor targeting peptide, cyclic Arg-Gly-Asp (cRGDyK), and Ce6, each bonded with HSA separately via amide bonds [175].…”
Section: Conjugation With Peptidesmentioning
confidence: 99%
“…22 Many studies have shown that iRGD enhances the tumor targeting and penetrating ability of conjugated therapeutic agents or nanovehicles. [23][24][25][26] In the present study, iRGD was fused to the C-terminus of ELP-D to have iRGD moieties on the surfaces of protein NPs. We evaluated the anti-cancer effects of paclitaxel (PTX)-loaded protein NPs having iRGD on cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…22 Many studies have shown that iRGD enhances the tumor targeting and penetrating ability of conjugated therapeutic agents or nanovehicles. 23–26…”
Section: Introductionmentioning
confidence: 99%